Keputusan Migrasi Sirkuler Pekerja Sektor Formal di Kota Medan - Muhammad Rizal (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This research conducted to analyze about factors influencing society decision of who live in beyond the city to migration of circular in Medan what variable of work Type, level of education, facilities of the city, the disadvantageous of villages, the ownership of land; influence the migration circular in the Medan. Population in this research is society working in formal sector in Medan, Technique of Intake of sample used is convience sampling that is by collecting data sample from a available information or source regardless of characteristic sample (Sekaran, 1992). From 200 quistioner which is spread there are 128 responder data which can be processed by using SPSS.10.0 regration Result of this research find there are influence between: Work type, level of education, city facilities, villages disadvantages, ownership of land; influence the migration circular in Medan with degree of probability 0,005 with the level significance 0.05, this research explain 12.3% migration of circular Medan affected by researched variable and rest is affected by other variable. This research also find that only variable of work type which by partial influence the society to conduct the migration to Medan with the probability 0.002 with the level significance 0.005%.Keywords: Migration Circular, The Disadvantageous Of Villages, City Attraction